Implementasi E-Banking Syariah pada Sistem Informasi Manajemen Industry Perbankan Syariah - reni (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2023)
The banking industry is one sector that relies heavily on information technology. Management information systems (SIM) are important in managing data and information in banking. The Islamic banking information system that is built will certainly increase the level of transactions and the outflow of digital money input only with debit or credit transactions carried out by customers or service users, with this information system, of course, banking performance must increase in the information needs of outsiders and the appearance of bank service features to attract as many customers as possible to facilitate transactions. The services and benefits of banking information systems are needed in the current area where competition between banks is tight in the use of information systems to attract customers using information technology. In maintaining its activities, Islamic banking cooperates with the field of technology to develop Islamic banking information systems by creating a special application (AAP) that can facilitate all existing transaction processes. The reliability of banking information systems is a major factor in running this type of banking, especially Islamic banking, which is currently increasing so that a reliable Islamic banking information system is needed. The purpose of this research is to implement a SIM on an Islamic bank for the bank. Keywords: management information system, E-Bangking, Sharing Banking Risk Manajment